Effect of training on knowledge, perception and risk reduction regarding infection control among nurses in selected teaching hospitals in Nigeria - Adekunbi Abosede Farotimi; Ezekiel Olasunkanmi Ajao; Chinomso Ugochukwu Nwozichi; Iyabo Yewande Ademuyiwa (Wolters Kluwer Medknow Publications, 2018)
Background: Healthcare workers, especially nurses, are at a high risk of infection. By complying with infection control measures, a lot of infections can be prevented. This study examined the effects of a training program on knowledge, perception, and risk reduction regarding infection control among nurses. Materials and Methods: This study adopted a pretest-posttest quasi-experimental design. The samples consisted of 87 participants comprising 42 nurses in the experimental group and 45 nurses in the control group. The instruments used for data collection were a questionnaire on knowledge about infection control and a questionnaire on perception about infection control. Results: Findings showed that the mean (SD) age in the experimental group was 34.92 (8.99) whereas that of the control group was 47.43 (6.60). The mean (SD) years of experience in the experimental group was 10.42 (9.95) years whereas in the control group it was 21.89 (8.72) years. Findings further revealed that 26 participants (62.90%) in the postintervention group had high knowledge level compared to the preintervention where none had high knowledge. A significant difference was observed between the mean perception score on infection control in the experimental and control groups (t = 17.12; p = 0.001). Conclusions: This study has shown that a training program is very effective and that all nurses should be exposed to infection control training to equip them with the necessary knowledge and skills with which to fight against the spread of infection in the healthcare setting.